Estimation of greenhouse gas emissions from Japanese healthy meals with different protein sources - Sameshima, Himeno; Akamatsu, Rie; Hayashi, Fumi; Takemi, Yukari (Frontiers in Sustainable Food Systems, 2023)
Introduction Diets that promote people’s health and environment-friendly are essential for achieving a sustainable society. Protein sources are the main contributors of greenhouse gas emissions (GHGE), and lower intakes of livestock meat and more intakes of poultry meat and legumes are recommended. Although Japanese consume less meat than other countries, it is unclear whether the GHGE of healthy Japanese meals is sufficient to solve climate change. In addition, most previous studies have focused on general household meals, not necessarily healthy meals. Therefore, we explored recommended food choices of protein sources in both healthy and environment-friendly meals. Methods We used data on healthy meals provided by retailers certified under the “Healthy Meal and Food Environment” Certification System. We first examined the number of main ingredients in the staple, main, and side dishes. We then compared the GHGE of meals with different combinations of main ingredients of main dishes (protein sources). To estimate the GHGE, we developed a database of GHGE per food weight for each food in the Standard Tables of Food Composition in Japan. Results Data on a total of 509 meals were considered in the analysis. The mean ± standard deviation of the total GHGE of one meal was 1044.7 ± 614.9 g-CO2 eq/650 kcal. The minimum and maximum values were 412.5 and 4268.5 g-CO2 eq/650 kcal, respectively. Regarding meat, chicken was more likely to be used in meals with low GHGE. Discussion The healthy meals with the lowest GHGE in this study had the potential to contribute to solving climate change. Although healthy meals in this study were created with the same nutrient level criteria, a large difference existed between the minimum and maximum GHGE and it depends on the choice of protein ingredients. The findings may be useful to develop food guide for Japanese taking environmental perspectives into account.